The Impact of the Sustainable Entrepreneurship on Non-Financial Business Performance: A Study of Start-Up Business Owner's Perception in an Indonesian University - Renita Kawuryan; Chang-Jung Lin (GoAcademica Research & Publishing, 2023)
The purpose of this research was to examine the impact of Sustainable Entrepreneurship on Non-Financial Business Performance for Start-up Business Owners in an Indonesian University. In this study, three dimensions of Sustainable Entrepreneurship- including People, Profit, and Planet- were measured subjectively by applying an eight-item dimensional scale from Soto Acosta. For Non-financial business performance, three dimensions were explored; Relationships with suppliers, Net fluctuation of employees, Customer complaints were measured by a nineteen-item scale from Škerlavaj. All the constructs in the study were modified to adhere within the five-point Likert type scale. The research used an explanatory approach with quantitative statistical techniques such as Mean, Standard Deviation, and Multiple Regression analysis. The total sample was 105 business owners incorporated into a business incubator in a University. Based on the calculation of the descriptive statistical analysis, the average of each variable calculation on People, Profit, Planet and Non-financial Business Performance show that most respondents tend to agree about the implementation of sustainable business practices within their businesses. This is indicated by the results of the overall grand mean, in the interval >3-4. The effect of each independent variable on the dependent variable of Non-financial Business Performance which includes its sub-dimensions (Relationship with suppliers, Net fluctuation of employees and Customer complaints) was done by utilizing the F-test. From the results of multiple linear regression analysis, it concludes that all of the dependent variables can be significantly influenced by independent variables People, Profit, and Planet.